Petrochronology of monazite and xenotime from emerald deposits in the Eastern Cordillera of Colombia: constraints on the hydrothermal evolution of the Cretaceous basin - Andrés Felipe González-Durán; Adam C. Simon; Robert Holder; Javier García-Toloza (Mineralium Deposita, 2026)
Lower Cretaceous strata of the Eastern Cordillera of Colombia host some of the world’s premier emerald deposits, yet the timing of mineralization—and its relationship to the tectonic evolution of the Cordillera—remains poorly constrained. We present high-resolution in situ U–Th–Pb petrochronology of monazite and xenotime from both the Eastern and Western Emerald Belts, revealing at least three stages of mineral growth: (1) authigenic crystallization during early burial and diagenesis (~ 140–120 Ma, Eastern Belt; ~125–100 Ma, Western Belt) (2) metamorphic recrystallization at ~ 120 Ma (Eastern Belt) and ~ 99 Ma (both belts) associated with peak basin temperatures; and (3) prolonged hydrothermal overprinting initiated by a major fluid pulse at ~ 85 Ma and persisting until ~ 37 Ma. Emeralds (± euclase) and associated REE minerals formed during this final stage in at least two distinct episodes. Our results document a multistage, episodic history of emerald mineralization, with REE redistribution closely linked to polyphase tectonothermal processes rather than a single mineralizing event. These findings refine the temporal framework for Colombian emerald formation, highlight the potential for REE recovery as a by-product of emerald mining, and underscore the importance of non-magmatic hydrothermal systems in sedimentary basins as potential sources of critical minerals.

Muigaia, a new Paleotropical genus of Convolvulaceae - Simon Wachira Ngima; Vivian Kathambi; Samuel Paul Kagame; Sushant More; Lauren A. Eserman; Rafael Felipe de Almeida; Benoit Loeuille; Marc S. M. Sosef; Patrick Chalo Mutiso; Higor Antonio-Domingues; Lars W. Chatrou; Ana Rita Simões (Kew Bulletin, 2026)
Summary A new genus of Convolvulaceae, Muigaia , is here proposed and fully revised, including molecular phylogenetic analyses, comprehensive morphological and palynological descriptions, identification keys, distribution maps and conservation assessments. It is a strictly paleotropical genus, occurring in Tropical Africa, Madagascar, India and Australia, and remarkably absent from the Malesian region. It is distinctive for the markedly angular stems; deeply palmately lobed, irregularly dissected leaves; leaf-like stipules at the base of the petiole; muricate, verrucose or cristate sepals; a 3-globose stigma and a 6-valved capsule. A revision of the species involved in this complex has resulted in the recognition of a total of seven species, including five new combinations, one new name ( M. shimpalei ) and one newly described species ( M. australiana ), endemic to Australia. The tropical African specimens of M. coptica , in particular, exhibit a wide range of morphological variation and should be investigated in detail. We expect that, now that Muigaia has been phylogenetically and morphologically circumscribed, further revisionary studies could focus on improving the species delimitation, and likely result in the discovery of additional new species to science.

Life cycle analysis of microalgae bioethanol production scenarios - João Felipe Freitag; Victória Dutra Fagundes; Viviane Simon; Rosana de Cássia de Souza Schneider; Luciane Maria Colla (Biomass and Bioenergy, 2026)

Impact of Diabetes on Oxidative Stress, Mitochondrial Function, and Neurological Outcomes Following Ischemic Stroke: A Sex-Based Experimental Analysis - Richard Simon Machado; Khiany Mathias; Cristiane Coral; David dos Santos; Sandra Regina Santana Aguiar Bonfante; Solange de Souza Stork; Anita Dal Bó Tiscoski; Victor Duílio Antunes Maragno; Alberto Martins Silva; Henrique Mautone Gomes; Isabela da Silva Lemos; Luana dos Reis Possa; et al. (Molecular Neurobiology, 2026)

Water mineralization in resource-limited locations - Andrés Felipe Sánchez Rendón; Simon Ponton; David Brassard; Emilie Bédard; Jason R. Tavares (Journal of Water Process Engineering, 2025)

Upregulating of organic acids in contrasting plant species results in moderation of high pH stress - Felipe E. Sepúlveda Olea; Ian T. Burke; Robert D. Hancock; Simon D.A. Pont; Douglas I. Stewart (Rhizosphere, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Supplemental Feeding as a Driver of Population Expansion and Morphological Change in Anna's Hummingbirds - Nicolas M. Alexandre; Faye G. Romero; Simon G. English; Eliza Grames; Felipe Garzón‐Agudelo; Kevin Epperly; Timothy Barnes; Donald R. Powers; Audrey E. Smith; Zoë Migicovsky; Laura Stein; Saron Akalu; et al. (Global Change Biology, 2025)
Bird beaks are highly adaptable, with the potential to undergo rapid morphological shifts in response to environmental change such as climatic variation or food availability. Anna's Hummingbirds ( Calypte anna ) have undergone dramatic population range expansions over the last 160 years into novel climatic regimes, where supplemental feeders and introduced plant species are frequented. We used museum specimens to measure and characterize the shape of Anna's Hummingbird bills, hypothesizing that the introduction of novel food sources and the colonization of colder climates were associated with distinct dimensions of beak morphology. We estimated feeder and Eucalyptus availability using data from archived newspaper databases and found that these two abundances are linked to population increases in Anna's Hummingbirds, while feeders were associated with changes to beak morphology. We found that bill size and shape changed with feeder use, exhibiting a more tapered and longer bill and a distinct maxillary constriction. In males, dorsal bill shape increased in pointedness, which may have provided an advantage with increased agonistic encounters at feeders. In contrast, bill size decreased in association with lower temperatures at higher latitudes. Our data document rapid morphological changes in the Anna's Hummingbird's bill induced by human‐caused environmental changes over the last century.

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Evaluating the suitability of large-scale datasets to estimate nitrogen loads and yields across different spatial scales - Andrés Felipe Suárez-Castro; Dale M. Robertson; Bernhard Lehner; Marcelo L. de Souza; Michael Kittridge; David A. Saad; Simon Linke; Rich W. McDowell; Mohammad Hassan Ranjbar; Olivier Ausseil; David P. Hamilton (Water Research, 2025)

Oxidative stress and mitochondrial dysfunction contributes to postoperative cognitive dysfunction in elderly rats dependent on NLRP3 activation - Sandra Bonfante; Martins Back Netto; Aloir Neri de Oliveira Junior; Khiany Mathias; Richard Simon Machado; Larissa Joaquim; Taina Cidreira; Marina Goulart da Silva; Guilherme Cabreira Daros; Lucinéia Gainski Danielski; Fernanda Gava; Isabela da Silva Lemos; et al. (Metabolic Brain Disease, 2024)

Impact of Quaternary Amazonian river dynamics on the diversification of uakari monkeys (genus Cacajao ) - Felipe Ennes Silva; Leilton Willians Luna; Romina Batista; Fabio Röhe; Chrysoula Gubili; Izeni P. Farias; Tomas Hrbek; João Valsecchi; Camila C. Ribas; Allan D. McDevitt; Simon Dellicour; Jean‐François Flot; et al. (Journal of Biogeography, 2024)
Aim The central and western Amazonia underwent several landscape changes during the Quaternary. Whereas the Riverine Barrier Hypothesis is traditionally used to explain the influence of rivers on speciation, processes such as river rearrangements have been overlooked to explain the geographic distribution and evolutionary history of Amazonia biota. Here, we tested how river rearrangements influenced the evolutionary history of uakari monkeys, genus Cacajao , a primate genus primarily associated with seasonally flooded forests in central and western Amazonia. Location Central and Western Amazonia. Taxon The genus Cacajao , including the black uakaris ( C. melanocephalus , C. ayresi , C. hosomi ); and the bald‐headed uakaris ( C. calvus , C. amuna , C. rubicundus , C. ucayalii , C. novaesi ). Methods We performed a continuous phylogeographic analysis using 77 cytochrome b sequences to identify the origin and dispersal of Cacajao lineages. We used genome‐wide SNP variation (ddRADseq) to investigate population structure, gene flow and demographic history in Cacajao populations and used digital elevation models to identify landscape and riverscape characteristics that may have influenced the geographic distribution of Cacajao . Results Our continuous phylogeographic reconstruction pointed out that the ancestral Cacajao lineage occupied the flooded forests of the Solimões River, in central Amazonia, at ~1.7 Mya and descendant lineages dispersed throughout central and western Amazonia more recently. We identified gene flow in both black and bald‐headed uakari populations, even across rivers considered barriers (e.g. the Negro River). Landscape analysis showed that river rearrangements influenced the geographic distribution and population structure in Cacajao . Historical demographic analyses suggest varied scenarios of population size changes among Cacajao monkeys consistent with periods of intense dynamism in flooded habitats and the formation of non‐flooded upland forests. Main Conclusion Our results support that the river rearrangements have shaped the geographic distribution and divergence of recently diverged Cacajao lineages. Landscape and riverscape changes, along with retractions of the flooded forests, isolated some Cacajao populations in floodplain areas. Our study also suggests that these events led to the recent changes in demographic histories in species with a restricted geographic distribution.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Aurantiochytrium sp. Meal as Feed Additive for Pacific White Shrimp Reared under Low Temperature and Challenged by WSSV in Association with Thermal Stress - Flávia Banderó Hoffling; Alex Silva Marquezi; Isabela Pinheiro; Cedric Simon; Artur Nishioka Rombenso; Walter Quadros Seiffert; Felipe do Nascimento Vieira; Delano Dias Schleder (Fishes, 2024)
A study was conducted to test the inclusion of Aurantiochytrium sp. meal in the rearing of Penaeus vannamei grown in a clear water system and at a suboptimal temperature of 22 °C. The doses tested were 0 (control), 1, 2, 3, and 4% at a stocking density of 100 shrimp/m3. Rearing was carried out with aeration and individual heaters, and seawater temperature was controlled with a chiller. After nine weeks, shrimp were weighed and hemolymph was collected for hemato-immunological tests, and growth performance were calculated. Shrimp raised at 22 °C and fed a 1% of dietary supplementation of Aurantiochytrium sp. meal were superior in immunological parameters. After the dietary assay, a total of 42 shrimps (10.9 ± 0.06 g) per treatment were infected with White Spot Syndrome Virus (WSSV). They were orally infected with 2.6 ± 106 virus particles per g of the animal, maintained at a suboptimal temperature of 22 °C for 108 h, and acclimated to an optimal temperature of 28 °C for an additional 48 h. At 7 days post infection, surviving shrimp were collected for hemato-immunological analysis. Cumulative mortality results showed that shrimp fed diets containing 3% and 4% Aurantiochytrium sp. meal had higher survival than other treatments when challenged with WSSV.

Enzyme-immobilized hierarchically porous covalent organic framework biocomposite for catalytic degradation of broad-range emerging pollutants in water - Nada Elmerhi; Khadega Al-Maqdi; Khawlah Athamneh; Abdul Khayum Mohammed; Tina Skorjanc; Felipe Gándara; Jesus Raya; Simon Pascal; Olivier Siri; Ali Trabolsi; Iltaf Shah; Dinesh Shetty; et al. (Journal of Hazardous Materials, 2023)

Bifidobacterium lactis CCT 7858 Improves Gastrointestinal Symptoms by Antibiotics Treatment: a Double-Blind, Randomized, Placebo-Controlled Trial - Monique Michels; Emily Córneo; Luana Cucker; Carla Sasso Simon; Gabriel Fernandes Alves de Jesus; Carolina Michels; Kristian Madeira; Ana Paula Voytena; Marina Rossetto; Fernanda Ramlov; Danusa de Castro Damásio; Felipe Dal-Pizzol (Probiotics and Antimicrobial Proteins, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Species delimitation in the Trichocentrum cepula (Oncidiinae, Orchidaceae) complex: a multidisciplinary approach - Antonio E. Camelo-Júnior; Alessandro W. C. Ferreira; Ivanilza M. Andrade; Simon J. Mayo; Felipe Nollet; José L. Silva; Maria C. Barros; Elmary Fraga; Edlley M. Pessoa (Systematics and Biodiversity, 2022)

Effects of different probiotic strains B. lactis, L. rhamnosus and L. reuteri on brain-intestinal axis immunomodulation in an endotoxin-induced inflammation - Monique Michels; Gabriel Fernandes Alves Jesus; Mariane Rocha Abatti; Emily Córneo; Luana Cucker; Heloisa de Medeiros Borges; Natan da Silva Matos; Luana Bezerra Rocha; Rodrigo Dias; Carla Sasso Simon; Ana Paula Lorenzen Voytena; Marina Rossetto; et al. (Molecular Neurobiology, 2022)

Role of climatic factors in the toxicity of fipronil toward earthworms in two tropical soils: effects of increased temperature and reduced soil moisture content - Thuanne Braúlio Hennig; Paulo Roger Lopes Alves; Felipe Ogliari Bandeira; Liziara da Costa Cabrera; Jonas Simon Dugatto; Marco Aurélio Tramontin da Silva; Dilmar Baretta (Environmental Science and Pollution Research, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Functional biogeography of Neotropical moist forests: Trait–climate relationships and assembly patterns of tree communities - Bruno X. Pinho; Marcelo Tabarelli; Cajo J. F. ter Braak; S. Joseph Wright; Víctor Arroyo‐Rodríguez; Maíra Benchimol; Bettina M. J. Engelbrecht; Simon Pierce; Peter Hietz; Bráulio A. Santos; Carlos A. Peres; Sandra C. Müller; et al. (Global Ecology and Biogeography, 2021)
Aim Here we examine the functional profile of regional tree species pools across the latitudinal distribution of Neotropical moist forests, and test trait–climate relationships among local communities. We expected opportunistic strategies (acquisitive traits, small seeds) to be overrepresented in species pools further from the equator, but also in terms of abundance in local communities in currently wetter, warmer and more seasonal climates. Location Neotropics. Time period Recent. Major taxa studied Trees. Methods We obtained abundance data from 471 plots across nine Neotropical regions, including c . 100,000 trees of 3,417 species, in addition to six functional traits. We compared occurrence‐based trait distributions among regional species pools, and evaluated single trait–climate relationships across local communities using community abundance‐weighted means (CWMs). Multivariate trait–climate relationships were assessed by a double‐constrained correspondence analysis that tests both how CWMs relate to climate and how species distributions, parameterized by niche centroids in climate space, relate to their traits. Results Regional species pools were undistinguished in functional terms, but opportunistic strategies dominated local communities further from the equator, particularly in the Northern Hemisphere. Climate explained up to 57% of the variation in CWM traits, with increasing prevalence of lower‐statured, light‐wooded and softer‐leaved species bearing smaller seeds in more seasonal, wetter and warmer climates. Species distributions were significantly but weakly related to functional traits. Main conclusions Neotropical moist forest regions share similar sets of functional strategies, from which local assembly processes, driven by current climatic conditions, select for species with different functional strategies. We can thus expect functional responses to climate change driven by changes in relative abundances of species already present regionally. Particularly, equatorial forests holding the most conservative traits and large seeds are likely to experience the most severe changes if climate change triggers the proliferation of opportunistic tree species.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Specialisation and diversity of multiple trophic groups are promoted by different forest features - Caterina Penone; Eric Allan; Santiago Soliveres; María R Felipe‐Lucia; Martin M Gossner; Sebastian Seibold; Nadja K. Simons; Peter Schall; Fons van der Plas; Peter Manning; Rubén D. Manzanedo; Steffen Boch; et al. (Ecology Letters, 2019)
While forest management strongly influences biodiversity, it remains unclear how the structural and compositional changes caused by management affect different community dimensions (e.g. richness, specialisation, abundance or completeness) and how this differs between taxa. We assessed the effects of nine forest features (representing stand structure, heterogeneity and tree composition) on thirteen above‐ and belowground trophic groups of plants, animals, fungi and bacteria in 150 temperate forest plots differing in their management type. Canopy cover decreased light resources, which increased community specialisation but reduced overall diversity and abundance. Features increasing resource types and diversifying microhabitats (admixing of oaks and conifers) were important and mostly affected richness. Belowground groups responded differently to those aboveground and had weaker responses to most forest features. Our results show that we need to consider forest features rather than broad management types and highlight the importance of considering several groups and community dimensions to better inform conservation.

Sarcopenia in a mice model of chronic liver disease: role of the ubiquitin–proteasome system and oxidative stress - Fabián Campos; Johanna Abrigo; Francisco Aguirre; Bruno Garcés; Marco Arrese; Saul Karpen; Daniel Cabrera; Marcelo E. Andía; Felipe Simon; Claudio Cabello-Verrugio (Pflügers Archiv - European Journal of Physiology, 2018)

Assessing two large area burnt area products across Australian Southern Forests - Mariela Soto-Berelov; Simon D. Jones; Elizabeth Clarke; Shanti Reddy; Vaibhav Gupta; Maria Luisa Cardoso Felipe (International Journal of Remote Sensing, 2018)

The characterization of anti-T. cruzi activity relationships between ferrocenyl, cyrhetrenyl complexes and ROS release - César Echeverría; Valentina Romero; Rodrigo Arancibia; Hugo Klahn; Ignacio Montorfano; Ricardo Armisen; Vincenzo Borgna; Felipe Simon; Rodrigo Ramirez-Tagle (BioMetals, 2016)

Cavβ2 transcription start site variants modulate calcium handling in newborn rat cardiomyocytes - Cristian Moreno; Tamara Hermosilla; Danna Morales; Matías Encina; Leandro Torres-Díaz; Pablo Díaz; Daniela Sarmiento; Felipe Simon; Diego Varela (Pflügers Archiv - European Journal of Physiology, 2015)

The angiotensin-(1–7)/Mas axis reduces myonuclear apoptosis during recovery from angiotensin II-induced skeletal muscle atrophy in mice - Carla Meneses; María Gabriela Morales; Johanna Abrigo; Felipe Simon; Enrique Brandan; Claudio Cabello-Verrugio (Pflügers Archiv - European Journal of Physiology, 2015)

Expression of the Mas receptor is upregulated in skeletal muscle wasting - María Gabriela Morales; Johanna Abrigo; Carla Meneses; Franco Cisternas; Felipe Simon; Claudio Cabello-Verrugio (Histochemistry and Cell Biology, 2015)

Determining the Feasibility of Establishing New Multiple-Use Marine Protected Areas in Chile - Felipe Vásquez-Lavín; Jeanne W. Simon; Ximena Paz-Lerdón (Ambio, 2013)

DNA-hsp65 Vaccine as Therapeutic Strategy to Treat Experimental Chromoblastomycosis Caused by Fonsecaea Pedrosoi - Isaque Medeiros Siqueira; Alice Melo Ribeiro; Yanna Karla de Medeiros Nóbrega; Karina Smidt Simon; Ana Camila Oliveira Souza; Márcio Souza Jerônimo; Florêncio Figueiredo Cavalcante Neto; Célio Lopes Silva; Maria Sueli Soares Felipe; Anamélia Lorenzetti Bocca (Mycopathologia, 2013)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Effects of Chronic Cortisol Administration on Global Expression of GR and the Liver Transcriptome in Sparus aurata - Mariana Teles; Sebastian Boltaña; Felipe Reyes-López; Maria Ana Santos; Simon Mackenzie; Lluis Tort (Marine Biotechnology, 2013)